2019
DOI: 10.21475/ajcs.19.13.06.p1669
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of low tetrahydrocannabinol (THC) Cannabis sativa L. cultivation in Victoria, Australia: Do we know enough?

Abstract: Late 2017, the ban on the cultivation and consumption of low tetrahydrocannabinol (THC) Cannabis sativa L. in Victoria, was lifted by the Federal Government of Australia. Its legalization presents the opportunity for Victoria to become a leading producer and distributer of these economically valuable hemp products. However, as a novel crop to Victoria, there is little information available for obtaining economically viable yields. Therefore, the objectives of this review were to firstly, develop an understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Basically, the adaptation of a variety depends largely on their sensitivity to photoperiod and temperature (Amaducci et al 2012;Hall et al 2012). Cannabis generally prefers high temperatures and a relatively long photoperiod (Cole & Zurbo 2008;Hall et al 2013;Hall et al 2014a;Humphries & Florentine 2019).…”
Section: Soil and Climatic Requirementsmentioning
confidence: 99%
See 4 more Smart Citations
“…Basically, the adaptation of a variety depends largely on their sensitivity to photoperiod and temperature (Amaducci et al 2012;Hall et al 2012). Cannabis generally prefers high temperatures and a relatively long photoperiod (Cole & Zurbo 2008;Hall et al 2013;Hall et al 2014a;Humphries & Florentine 2019).…”
Section: Soil and Climatic Requirementsmentioning
confidence: 99%
“…Furthermore, Cannabis possesses the ability to produce some allelochemicals which could suppress the growth and establishment of weeds (Campiglia et al 2017). Therefore, continuous cultivation of Cannabis for several years in the same piece of lands negatively affects the seedbanks for problematic weeds (Humphries and Florentine 2019). It has been reported that C. sativa is able to produce a germination inhibiting essential oil, which could suppress some agricultural weeds by acting as an effective botanical herbicide (Agnieska et al 2016).…”
Section: Weed Managementmentioning
confidence: 99%
See 3 more Smart Citations